Constitutional revolution - Jacobsohn, Gary J., 1946-; Roznai, Yaniv (Yale University Press, 2020)
Few terms in political theory are as overused, and yet as under-theorized, as constitutional revolution. In this book, Gary Jacobsohn and Yaniv Roznai argue that the most widely accepted accounts of constitutional transformation, such as those found in the work of Hans Kelsen, Hannah Arendt, and Bruce Ackerman, fail adequately to explain radical change. For example, a "constitutional moment" may or may not accompany the onset of a constitutional revolution. The consolidation of revolutionary aspirations may take place over an extended period. The "moment" may have been under way for decades-or there may be no such moment at all. On the other hand, seemingly radical breaks in a constitutional regime actually may bring very little change in constitutional practice and identity. Constructing a clarifying lens for comprehending the many ways in which constitutional revolutions occur, the authors seek to capture the essence of what happens when constitutional paradigms change